Role of Stakeholders’ Knowledge in Designing Successful Interpretation Services in Conserving Natural Resources - Rachmawati, Eva (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
The goals of interpretation activities can be achieved if interpretation service planning is carried out correctly. The planning process could succeed if the planner has adequate knowledge and understanding of interpretation services. Knowledge and understanding are crucial to determining what to do. This research aims to measure the knowledge and understanding of tourism managers and organizers, as well as their interpretations of important aspects of interpretation, including interpretation resources, visitors' characteristics, and interpretation techniques. The research method used is qualitative. Data were collected through structured interviews with 15 informants (managers and organizers of interpretation activities). The interviews reveal that the managers and implementers of tourism activities and/or interpretations already possess a good knowledge and understanding of the interpretation resources available in the area, particularly regarding their tangible and intangible values. However, they still need to understand the universal concept of these resources. Additionally, all informants still need to gain more knowledge and understanding of the characteristics and backgrounds of visitors, as well as interpretation techniques. Only 80% of informants were aware of interpretation pathways, and 60% were aware of interpretation programs. This limited knowledge and understanding are assumed to be one of the inhibiting factors in the formulation of a good interpretation service. Ultimately, it becomes an inhibiting factor in creating public awareness regarding preserving natural resources. This research highlights the need to enhance the knowledge and understanding of interpretation stakeholders regarding the key aspects required for planning interpretation services through training, workshops, or formal education.